1998
DOI: 10.1128/jvi.72.4.3370-3376.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Cytopathogenic, Apoptosis-Inducing Variant of Hepatitis A Virus

Abstract: A cytopathogenic variant of hepatitis A virus (HAVcyt/HB1.1) was isolated from persistently infected BS-C-1 cells by serial passages in FRhK-4 cells. This virus shows a rapid replication pattern and high final titers are obtained, which are main characteristics of cytopathogenic HAVs. Sequencing of the nontranslated regions and the coding regions for 2ABC and 3AB revealed that mutations are distributed all over these regions and that certain mutated sites correspond to those in other cytopathogenic HAV variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 31 publications
4
35
0
Order By: Relevance
“…Previous investigations have demonstrated that a cp strain of HAV, HAVcyt/HB1.1, derived from the cc strain HM175, induced apoptosis in 2-5% of the cells by 120 h post-infection (pi), increasing to 37.5% by 14 days pi (Brack et al, 1998). Similar slowly developing cpe and apoptosis were reported in cells infected with another cp strain, HM175/24a (Gosert et al, 2000).…”
Section: Virus Replication and Apoptosis In Infected Cellssupporting
confidence: 57%
See 4 more Smart Citations
“…Previous investigations have demonstrated that a cp strain of HAV, HAVcyt/HB1.1, derived from the cc strain HM175, induced apoptosis in 2-5% of the cells by 120 h post-infection (pi), increasing to 37.5% by 14 days pi (Brack et al, 1998). Similar slowly developing cpe and apoptosis were reported in cells infected with another cp strain, HM175/24a (Gosert et al, 2000).…”
Section: Virus Replication and Apoptosis In Infected Cellssupporting
confidence: 57%
“…ing virus, viral genomic RNA was amplified using primers directed to the 5 NTR (Panel E). The results clearly show the presence of undiminished amount of viral genome in clone 1 cells after several months of cultivation, with no indication that the virus has acquired the 14 base repeat present in the genome of 18f and other cp strains (Brack et al, 1998;Zhang et al, 1995).…”
Section: Effect Of Interferon Pretreatment On Rna Degradationmentioning
confidence: 88%
See 3 more Smart Citations